A Project feasibility study Multi-Fuel Energizer - Antonio, Ashley S. (College of Engineering, 1993)
The Multi-Fuel Energizer is a fuel saving and anti-pollution device. Simply put, when installed in a diesel vehicle engine, this device helps save fuel and eliminate smoke belching. Governing these benefits is the principle of better fuel combustion through heating .Metro Manila being the most congested city in the country as the target market of the MFE. The market for the MFE is made favorable by the growing diesel consumption and the worsening air pollution in the country. Of the total market, only 2.5% is targeted for the first two years of operations. The technical study shows that a simple machine shop set-up is sufficient for the production of the MFE. The availability of this technology, of ample suppliers, and of a possible plant site within the Metro Manila makes the project highly feasible. The financial study indicated a very lucrative business ahead of the company. After the initial loan to finance its early operations, the company would generate increasing incomes. Analysis of the forecasted financial statements reiterated the company's ability to make a profit, promptly pay short and long term debts, keep its assets liquid, and provide a justification for an investment. The social profitability study provided the most encouraging results for the company. Besides the normal benefits to individuals and the government given by any business venture which increases income, pays taxes and taps local suppliers; the establishment of the company will indirectly increase the country's foreign reserves and greatly benefit the environment.